Exploring Differentiated Intervention Models of Rural Tourism for Rural Revitalization in China - Lu, Linlin (Transactions on Social Science, Education and Humanities Research, 2024)
This article discusses the policy intervention issues faced by rural tourism development in China, which often suffers from a lack of diversity and fails to generate substantial economic and social benefits. To address this situation, the study conducts a comprehensive review of rural tourism literature from both domestic and international sources, and identifies four distinct intervention models, namely, architectural intervention, homestay intervention, red tourism intervention, and religious intervention. Successful cases as illustrations for each model are analyzed and explained. Additionally, the article compares these models across seven dimensions: stakeholders, location, materiality, authenticity, economic effects, social effects, and replicability. This multidimensional analysis reveals the characteristics, impacts, and applicability of each model. The architectural intervention emphasizes attracting tourists through unique architectural projects, heavily relying on the reputation of architects. The homestay intervention demonstrates greater flexibility and wider applicability. This study provides valuable insights into the development of context-specific rural tourism through the principle of place-based development.